A heuristic to capture multi-directional lateral tactile perception - Placencia, Greg; Rahimi, Mansour; Khoshnevis, Behrokh (Theoretical issues in ergonomics science, 2012)
Multi-directional tactile perception adds significant complexity when interpreting haptic experimental data. In perceiving tactile stimulus direction, we often observe a lack of one-to-one stimulus-response compatibility, mostly due to confounding sensations that reinforce and/or distort a primary stimulus. This study presents the development of a metric to capture multi-directional lateral tactile perception on a finger pad. Sixty-two subjects rated the direction and magnitude of lateral motion from a single probe moving in one of the eight possible directions. A heuristic based on a vector matrix was developed to capture and integrate the relative contribution of each subject's rated directional perception in x-y coordinates. This article explains the theoretical underpinnings and the justifications for this heuristic and highlights the usefulness of this approach for future haptic system designs.